METHODS OF JUDICIAL PROTECTION OF BUSINESS ENTITIES - Похиленко, Ірина Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose: the purpose of the article is to determine the methods of judicial protection of business entities and, on the basis of the analysis of legal literature and normative legal acts, to propose an author’s definition of the said concept. Research methods: the following methods are applied. Formal-logical – for the formation of new concepts, their classification; eliminating inaccuracies and contradictions, etc. Formal-dogmatic, or legal method, based on the use of rules of formal logic for knowledge of law, is a traditional, inherent in legal science, since it proceeds from its nature. Its essence is in the formulation and disclosure of legal concepts, the construction of legal structures, and clarification of the actual content of the law. This method was used in the analysis of methods of judicial protection of business entities. At all stages of scientific research the dialectical method is used. This method determines the paths of any scientific study. It helps to explore all the phenomena in the relationship, interdependence. Comparative method involves comparing single-order legal concepts, phenomena and processes to establish similarities and account for differences between them. Results: summarizing the mentioned above, it is possible to conclude that the issue of legal conceptual apparatus of economic law improving remains relevant and requires further scientific research, in particular, in the definition of the concept of «methods of judicial protection of business entities». That is why, the following definition of methods of judicial protection of business entities has been suggested as the activity of judicial authorities in accordance with the established jurisdiction and the form of judiciary aimed at restoring (recognition) of violated (disputed) rights and legitimate interests of business entities, which is performed in the law, contract, or other method that is not contrary to the law if the court concludes that no statutory remedy is effective in the legal relationship at issue, or if volunteering the request will effectively protect the rights or interests. Discussion: correlation of judicial remedies with other elements of the protection of the rights of business entities.